Drowning 'Truths': Contrasting experiential-experts' perceptions with official-experts drowning reports on Australia's hazardous coasts. (August 2020) - Kamstra, Peter; Cook, Brian; Kennedy, David; Rijksen, Eveline; Daw, Shane
Graphical abstract: Drawing on the experiential fishers' accounts, this figure shows how experiential-experts knowledge can be used to expand the application of the sandy beach safety principles to the context of rock fishing (i.e., how risk is known). It maps out experiential-experts' drowning typology (green), official-experts drowning types (blue) and the importance of collective framings of risk (yellow) that reflect the safety principles of 'how to avoid and respond to risk'. This includes contributing to the growing body of coastal risk literature that highlights the risk of bystander (i.e., collective) rescues, which, in this context, appears to be encouraging submerged, inexperienced fishers to regain access to the shore platforms. Image 1 Highlights: How rock fishers enter the sea is unknown in the majority of drownings. Inexperience is framed as a chief contributor to how fishers enter the sea and drown. Fishers' perceptions reflect practice-based knowledge rather than physical risks. Fishers demonstrate that safe fishing practice is contingent on not entering the sea. Fishing with experts in situ might help inexperienced fishers learn how to avoid risk.